Access to robot-assisted total knee arthroplasty varies significantly by race/ethnicity - Jessica Schmerler; Victoria E. Bergstein; Whitney Kagabo; Harpal S. Khanuja; Julius K. Oni; Vishal Hegde (Knee Surgery & Related Research)
Abstract Background Racial/ethnic disparities in access to total knee arthroplasty (TKA) have been extensively demonstrated. Over the past several years, there has been a rapid increase in the utilization of robot-assisted TKA (RA-TKA). Therefore, this study sought to determine whether previously established racial/ethnic disparities extend to access to RA-TKA relative to conventional TKA. Methods Patients who underwent TKA from 1 January 2022 to 31 December 2022 were identified in the National Surgical Quality Improvement Program database. Patients were stratified by whether they underwent RA-TKA. Multivariable logistic regressions, controlling for demographics and comorbidities significantly different on univariate analysis, were constructed to determine whether race/ethnicity was associated with likelihood of undergoing RA-TKA relative to conventional TKA. Results Of the 47,898 patients who underwent TKA in 2022, 8560 (17.9%) underwent RA-TKA. On multivariable analysis, Black, Hispanic, Asian, and all other races were significantly less likely than white patients to undergo RA-TKA relative to conventional TKA (OR 0.65, 95% CI 0.59–0.70, P < 0.001; OR 0.70, 95% CI 0.64–0.77, P < 0.001; OR 0.65, 95% CI 0.55–0.76, P < 0.001; OR 0.78, 95% CI 0.66–0.92, P = 0.003, respectively). Conclusions The results of this study demonstrate that non-white race is associated with a significantly lower likelihood of undergoing RA-TKA relative to conventional TKA. Importantly, this reduced access to RA-TKA may represent a broader disparity in access to emerging technologies and modern care. Future work should endeavor to identify drivers of this disparity to better understand minority access to emerging technologies in TKA. Level of evidence III.